WRITING AN INTERNATIONAL JOURNAL ARTICLE BY INDONESIAN COLLEGE TEACHERS: WHAT TO WORRY ABOUT - Wigati, Fikri Asih; Iman, Candra Hayatul (Jurnal Bahasa Inggris, 2018)
This study addresses the question of the respondents ?problems in writing a research article. The participants in this study were six teachers who enrolled in the journal writing class in a university in Karawang. Three of them are ready with submission, but three others are not. The data were collected by way of two techniques: analysis of the article portfolio and interviews. The data were later codified and triangulated in order to reveal the participants? technical problems based on the research article elements and participants? psychological interference. The findings show that the respondents still had problems in achieving the communicative purposes of the journal article elements. In general their problems were in giving justifications. Their writing also tend to be failed to spot the justification of their choice of the research methodology. They still missed to fill the gap with the previous researches, missed the mark to give interpretation on the results and discussion section, and do not offer recommendation in the conclusion. Likewise, the participants also have some of psychological interference in composing and submitting their article.